Spectrum of RB1 Mutations in Argentine Patients: 20-years Experience in the Molecular Diagnosis of Retinoblastoma1. (4th January 2013) - Ottaviani, Daniela; Parma, Diana; Giliberto, Florencia; Ferrer, Marcela; Fandino, Adriana; Davila, Maria Teresa; Chantada, Guillermo; Szijan, Irene
ABSTRACT: Background: Retinoblastoma is a hereditary cancer of childhood caused by mutations in the RB1 tumor suppressor gene. An early diagnosis is critical for survival and eye preservation, thus identification of RB1 mutations is important for unequivocal diagnosis of hereditary retinoblastoma and risk assessment in relatives. Methods: We studied 144 families for 20 years, performing methodological changes to improve detection of mutation. Segregation analysis of polymorphisms, MLPA, FISH and cytogenetic assays were used for detection of "at risk haplotypes" and large deletions. Small mutations were identified by heteroduplex/DNA sequencing. Results: At risk haplotypes were identified in 11 familial and 26 sporadic cases, being useful for detection of asymptomatic carriers, risk exclusion from relatives and uncovering RB1 recombinations. Ten large deletions (eight whole gene deletions) were identified in six bilateral/familial and four unilateral retinoblastoma cases. Small mutations were identified in 29 cases (four unilateral retinoblastoma patients), being the majority nonsense/frameshift mutations. Genotype-phenotype correlations confirm that the retinoblastoma presentation is related to the type of mutation, but some exceptions may occur and it is crucial to be considered for genetic counseling. Three families included second cousins with retinoblastoma carrying different haplotypes, which suggest independent mutation events. Conclusion: This study enabled us to obtain information about molecular and genetic features of patients with retinoblastoma in Argentina and correlate them to their phenotype.